The SAGE handbook of political science. 3 - Berg-Schlosser, Dirk; Badie, Bertrand; Morlino, Leonardo (London : SAGE Publications Ltd, 2020)
The SAGE Handbook of Political Science presents a major retrospective and prospective overview of the discipline. Comprising three volumes of contributions from expert authors from around the world, the handbook aims to frame, assess and synthesize research in the field, helping to define and identify its current and future developments. It does so from a truly global and cross-area perspective. Chapters cover a broad range of aspects, from providing a general introduction to exploring important subfields within the discipline. Each chapter is designed to provide a state-of-the-art and comprehensive overview of the topic by incorporating cross-cutting global, interdisciplinary, and, where this applies, gender perspectives. The Handbook is arranged over seven core thematic sections: Part 1: Political Theory; Part 2: Methods; Part 3: Political Sociology; Part 4: Comparative Politics; Part 5: Public Policies and Administration; Part 6: International Relations; and Part 7: Major Challenges for Politics and Political Science in the 21st Century.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Political science -- Handbooks, manuals, etc